2015
DOI: 10.1007/978-3-319-21993-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Fungi and Their Potential for Biogas Production

Abstract: Plant biomass is the largest reservoir of environmentally friendly renewable energy on earth. However, the complex and recalcitrant structure of these lignocellulose-rich substrates is a severe limitation for biogas production. Microbial pro-ventricular anaerobic digestion of ruminants can serve as a model for improvement of converting lignocellulosic biomass into energy. Anaerobic fungi are key players in the digestive system of various animals, they produce a plethora of plant carbohydrate hydrolysing enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 108 publications
1
53
0
Order By: Relevance
“…This could explain that the higher cellulase production in R2 could be a result of the higher fungal population in the rumen of animal fed on lignified forage (wheat straw) and the higher number of Cyllamyces and Neocallimastix plus the presence of Piromyces .This speculation in agreement with Gordon and Phillips , who indicated that the most rapid degradation of fibrous plant tissues was observed using Piromyces strains together with Neocallimastix and Orpinomyces .Furthermore, administration of Orpinomyces and Piromyces to lactating buffalo enhanced the digestibility of dry matter, crude protein, neutral detergent fiber, acid detergent fiber and increased milk yield and milk fate yield . Lignin‐embedded cellulose and hemicellulose represent a physical barrier against microbial and enzymatic attack . Rumen anaerobic fungi have the ability to degrade and separate the plant cell wall through rhizoidal growth and producing lignocellulosic enzymes cocktail .…”
Section: Discussionsupporting
confidence: 78%
“…This could explain that the higher cellulase production in R2 could be a result of the higher fungal population in the rumen of animal fed on lignified forage (wheat straw) and the higher number of Cyllamyces and Neocallimastix plus the presence of Piromyces .This speculation in agreement with Gordon and Phillips , who indicated that the most rapid degradation of fibrous plant tissues was observed using Piromyces strains together with Neocallimastix and Orpinomyces .Furthermore, administration of Orpinomyces and Piromyces to lactating buffalo enhanced the digestibility of dry matter, crude protein, neutral detergent fiber, acid detergent fiber and increased milk yield and milk fate yield . Lignin‐embedded cellulose and hemicellulose represent a physical barrier against microbial and enzymatic attack . Rumen anaerobic fungi have the ability to degrade and separate the plant cell wall through rhizoidal growth and producing lignocellulosic enzymes cocktail .…”
Section: Discussionsupporting
confidence: 78%
“…Veronika Dollhofer, Sabine Marie Podmirseg, Tony Martin Callaghan, Gareth Wyn Griffith and Kateřina Fliegerová et al [9] Anaerobic Fungi and Their…”
Section: Review Of Literaturementioning
confidence: 99%
“…The synergistic relation between anaerobic fungi and archaea in the gut of herbivores enables the reproduction of these microorganisms and also provides simple carbon and nitrogen compounds that are absorbed by the host [3]. Although anaerobic fungi comprise only a fraction of the gut microbiome in herbivores ( 8%), they are believed to be important players in the deconstruction of plant biomass, through a combination of enzymatic deconstruction and physical disruption via invasive growth of the rhizoids [2] (Figure 1).…”
Section: Spotlightmentioning
confidence: 99%
“…In anaerobic fungi, cellulases, hemicellulases, and CBMs can be complexed to dockerin proteins. A scaffolding protein has not been conclusively identified in anaerobic fungi; neither it is known how they may be associated with the fungal cell wall [3,5]. Micrograph of typical growth habit of anaerobic fungi, including rhizoids.…”
Section: Spotlightmentioning
confidence: 99%